(untitled) (International Journal of Engineering and Computer Science, 2017)
Open Source Dashboard Technology plays an imperative role to integrate IEDSS (Intelligent Decision Support System) in the establishment of the higher education in technology for revolutionized decision making. Because of modern factors, decision making has become complex requiring knowledge of business, data, and data representation; hence an intelligent computerized system is required. “An IEDSS is an intelligent information system that reduces the time in which decisions are made in an environmental domain and improves the consistency and quality of those decisions [Haagsma & Johanns, 1994]”. Decision-makers try to apply new strategies and use new tools to convert data into useful information that would contribute to managerial problem-solving. Decision makers require reports that are accurate, timely, and which give the whole “business picture”. Dashboard Technology and Intelligent Decision Support System (IEDSS) systems come to the rescue of decision makers. This paper proposes the integration of Open Source Dashboard Technology and IEDSS to improve the quality and efficiency of higher education’s systems. The dashboard enables executives to measure, monitor and manage organizational performance more effectively. If Dashboard Technology and IEDSS are applied to higher education processes, it would help to improve students’ performance, their life cycle management, selection of prospective students, course design, selection of courses to measure their retention rate, infrastructure, and development and the grant fund management of an institution. This is an approach to examine the effect of using open source dashboard technology and IEDSS for Higher Education Institution in strategic planning. Finally, an IEDSS system for higher education planning is introduced to illustrate and evaluate the use of dashboard technologies as intelligent decision-making tools.